68Ga-PSMA-11 PET/CT versus 68Ga-PSMA-11 PET/MRI for the detection of biochemically recurrent prostate cancer: a systematic review and meta-analysis - Huang, Ruizhe; Li, Yizhen; Wu, Haowen; Liu, Boyi; Zhang, Xuanjun; Zhang, Zhongxi (Frontiers in Oncology, 2023)
Purpose Our aim was to conduct a meta-analysis and systematic review in order to compare the diagnostic efficacy of 68Ga-PSMA-11 PET/CT and 68Ga-PSMA-11 PET/MRI in patients with biochemically recurrent after radical prostatectomy and biochemically recurrent prostate cancers (BCR) after hybrid RT and RP. Methods Up until February 2023, we searched PubMed, Embase, and Web of Science for pertinent papers. Studies examining the utility of 68Ga-PSMA-11 PET/CT or PET/MRI as a screening tool for biochemically recurrent prostate cancer were included. To measure heterogeneity, we employed the I2 statistic. In cases of substantial heterogeneity (I2 > 50%), we used the random effect model to produce a forest plot. In other cases, we utilized the fixed model. Furthermore, we assessed the quality of the studies included using the Quality Assessment of Diagnostic Performance Studies (QUADAS-2) method. Results In total, 37 studies involving 8409 patients were examined. For 68Ga-PSMA-11 PET/CT and 68Ga-PSMA-11 PET/MRI, the combined total detection rate was 0.70 (95% CI: 0.65-0.75) and 0.71 (95% CI:0.67-0.75), respectively. 68Ga-PSMA-11 PET/CT and 68Ga-PSMA-11 PET/MRI did not substantially differ in terms of the overall detection rate for BCR (P = 0.58). The detection rate was unaffected by the PSA values (all P > 0.05). Conclusion The diagnostic efficacy of 68Ga-PSMA-11 PET/CT appears to be equivalent to that of 68Ga-PSMA-11 PET/MRI in detecting biochemically recurrent prostate cancer. Nonetheless, it should be noted that not all studies have used pathological biopsies as the gold standard. Therefore, additional larger prospective studies are needed to address this issue.